Expressing infinite matrices as sums of idempotents - Słowik, R. (Ukrains’kyi Matematychnyi Zhurnal, 2017)
Let M_Cf (F) be the set of all column-finite N × N matrices over a field F. The following problem is studied: what elements of M_Cf (F) can be expressed as a sum of idempotents? The result states that every element of M_Cf (F) can be represented as the sum of 14 idempotents.